Practical aspects of psychological work with internally displaced first-year students - Lytvynenko, Olena (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2019)
The concept of complex psychological adaptation of first-year students for student life is presented. Theories of adaptability of adolescents and adolescents and the concept of their adaptation to new minds of life and activity are generalized. The results of the empirical study of the individual-psychological qualities of the freshmen, the features of their social interaction and academic motivation are described. The experience of the psychological support of the process of adaptation of students who are internally displaced to study at a university is analyzed. Their true personal and character peculiarities, ways of adapting to the situation and responding to adverse influences from the external environment are determined. The perspective circle of researches in the field of psychological support and support of internally displaced students is outlined. Adaptation to learning has been found to be a complex process of learning the norms and rules of an educational institution, forging friendships with one-groupers, and for constructive relationships with teachers; development of strategies of educational activity and initial activity. The article determines that the adaptation of internally displaced first-year students to study should come as an active tertiary adaptation of students to the higher education institutions, in the process of developing students' skills and ability to organize their understanding, and life, the system of working with professional self-education and self-education of professionally significant qualities of personality. It has been found that the process of adaptation to university education is a complex system of transformations that occur with a person in accordance with changes in the minds of existence. The beginning of a student's life is connected with numerous social changes; replacement of existing attitudes and stereotypes; stressful situations. For some students, this can lead to the substitution of a real sense of adulthood by activities such as freedom to attend classes, unsystematic homework, and so on. All of this can, over time, be transformed into a reluctance to study, attend a school, and participate in one's social life.
Keywords: adaptation of first-year students; internally displaced people; adaptive resources; adaptive capacity; educational process